2003
DOI: 10.1381/096089203322190871
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Functioning Before and After Laparoscopic Adjustable Gastric Banding: a Cross-Sectional Study

Abstract: LAGB could be a long-term solution to morbid obesity with regard to both weight and QoL outcome. The findings of our study emphasize the importance of including social QoL variables in outcome research. They further suggest that when the follow-up duration increases, especially in patients who are single, intervention and consultation should be simultaneously directed at weight and psychosocial variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 24 publications
3
34
0
1
Order By: Relevance
“…Several authors showed an improving mental health and quality of life by the first year that eroded over the subsequent years. [22][23][24][25][26][27] In our cross-sectional study, performed a mean of 8.7 years after the operation, we were able to show that a more impaired health and psychological status was present in those operated more than 5 years ago compared to subjects operated more recently. The time lapse since operation played an important role as health status scores showed a higher physical, emotional and social dysfunction in those operated more than 5 years ago and out of the psychological features sensitivity was also more present in these subjects.…”
Section: Discussionmentioning
confidence: 55%
“…Several authors showed an improving mental health and quality of life by the first year that eroded over the subsequent years. [22][23][24][25][26][27] In our cross-sectional study, performed a mean of 8.7 years after the operation, we were able to show that a more impaired health and psychological status was present in those operated more than 5 years ago compared to subjects operated more recently. The time lapse since operation played an important role as health status scores showed a higher physical, emotional and social dysfunction in those operated more than 5 years ago and out of the psychological features sensitivity was also more present in these subjects.…”
Section: Discussionmentioning
confidence: 55%
“…The questionnaire has a five-point Likert rating format, ranging from 1 (almost never) to 5 (almost always). The psychometric characteristics of the OPSQ, established in a sample of 287 patients before and after (surgical or dietary) treatment for (severe) obesity, are satisfactory [21].…”
Section: Instrumentsmentioning
confidence: 99%
“…The actual, expected, and past psychosocial states were measured using the "Obesity Psychosocial State Questionnaire" (OPSQ) [21]. The OPSQ measures seven domains: "physical function" (15 items, e.g., "to kneel or stoop easily"), "mental well-being" (six items, e.g., "to feel depressed"), "physical appearance" (nine items, e.g., "to feel fat when photographed"), "social acceptance" (four items, e.g., "to be singled out because of my weight"), "self-efficacy regarding eating and weight control" (three items, e.g., "to feel helpless about my eating behavior"), "intimacy" (four items, e.g., "to have sexual problems because of my weight"), and "social network" (two items, e.g., "to visit friends and acquaintances").…”
Section: Instrumentsmentioning
confidence: 99%
“…Bariatric surgery is reported to be the most effective method for achieving dramatic, long-term weight loss and is only indicated for the morbidly obese (Bocchieri et al, 2002a;Dziurowicz-Kozlowska, Wierzbicki, Lisik, Wasiak, & Kosieradzki, 2006;Puzziferri, 2005;van Hout, Fortuin, Pelle, & van Heck, 2008). The morbidly obese includes persons who may be classified as having Class II obesity with significant physical comorbidities and Class III obesity (Bocchieri, Meana, & Fisher, 2002a;Larsen et al, 2003;Dziurowicz-Kozlowska et al, 2006;Shai, Henkin, Weitzman, & Levi, 2003;WHO, 2000). Individuals who elect to undergo bariatric surgery are required to make several lifestyle changes (e.g., dietary choices and eating habits) prior to surgery and are expected to maintain adherence to those changes following surgery in order to maximize and maintain weight losses initiated by the effects of the surgery (Alvarado et al, 2005;Mechanick et al, 2008).…”
Section: Behavioral Weight Management Behavioral Weight Management Pmentioning
confidence: 99%